Subatomic Science of the Word in Quânticos da Incerteza[Uncertainty Quantics] by André Carneiro - Martinez, Luciana (Universidad Pedagógica y Tecnológica de Colombia, 2018)
In the poetry book Quânticos da Incerteza (2007) the writer (painter, photographer and film-maker) André Carneiro brings the conceptual universe of quantum mechanics into play (Heisenberg’s indeter- minacy principle, fundamentally) in order to point out reflective inflections on the uses and status of the word. In this text, Carneiro, the undeniable dean of Brazilian science fiction, brings together and arti- culates the conceptions of two symbolic orders that have been divided since the Age of Enlightenment: science and poetry